QTAIM and stress tensor interpretation of the (H2O)5 potential energy surface. Issue 31 (3rd October 2016) - Xu, Tianlv; Farrell, James; Xu, Yuning; Momen, Roya; Kirk, Steven R.; Jenkins, Samantha; Wales, David J.
Abstract : Using the quantum theory of atoms in molecules a near complete combined directed spanning quantum topology phase diagram (QTPD) was constructed from the nine (H2 O)5 reaction‐pathways and five unique Poincaré–Hopf solutions that were found after an extensive search of the MP2 potential energy surface. Two new energy minima that were predicted from earlier work are found and include the first (H2 O)5 conformer with a 3‐DQT quantum topology. The stress tensor Poincaré–Hopf relation indicated a preference for 2‐DQT (H2 O)5 topologies as well as the presence of coupling between shared‐shell OH BCPs to the hydrogen‐bond BCPs that share an H NCP. The complexity of the near complete combined QTPD was explained in terms of the O…O bonding interactions that were found in six of the nine (H2 O)5 reaction‐pathways and for all points of the combined QTPD. The stabilizing role of the O…O bonding interactions from the values of the total local energy density was explored. © 2016 Wiley Periodicals, Inc. Abstract : A directed Quantum topology Phase Diagram (QTPD) of the (H2 O)5 potential energy surface is created from QTAIM analysis. Two new energy minima that were predicted from earlier work include the first (H2 O)5 conformer with a 3‐DQT quantum topology. New insights into the stabilizing role of the O…O bonding interactions along a reaction‐pathway are found to explain the complexity of the (H2 O)5 near complete directed QTPD.